La violencia contra la mujer: Objeto - sujeto referencial para representación de obras pictóricas - Campoverde Granda, Evelyn Johanna (2022)
In the present investigation: Violence against women: referential object - subject for the representation of pictorial works, expressionist painting was analyzed that will serve to create the pictorial proposal and understand the artistic, aesthetic and philosophical foundations. Likewise, put special emphasis on the internal emotions of women, called human existence. Regarding the objectives, it is important to know about the foundations of expressionist painting, both artistically and aesthetically, as well as in relation to the foundations of pictorial production. It is essential to have knowledge about the processes of expressionist pictorial creation, since it is based on physical and psychological violence against women; This leads to the post-production process of the pictorial proposal and the exhibition of the pictorial sample. The subject in question is of an artistic nature, in which the inductive and deductive method is applied, which is analyzed, classified and understood; the iconographic method that is analyzed in the reference works has a sociocultural context; As for the experimental, graphic and plastic expression is used from the idea of the sketch. The field modality is also used to collect visual information about the subject, in which preparatory drawings, sketches and sketches are made, taking Edvard Münch and Paula Rego as references. At the end of the investigation, it is concluded that it is necessary to know about the artistic, aesthetic and philosophical foundations of expressionism, since, based on this, the pictorial proposal is made, representing violence against women, both in the physical field as psychological. Keywords: Painting, expressionism, violence against women, object-subject